Belleza Florista / Ledyiana Nasa Tutom ... [et. al] - Tutom, Ledyiana Nasa; Abdullah, Norazlina; Mohd Fadzil, Nurul Aida; Reynold, Reyquel Zelda (2019)
Belleza Florista is a start-up flowers nursery and shop establishment located in East Malaysia. Belleza Florista expects to catch the interest of a regular loyal customer base with its broad variety of fresh flowers that planted by our own in our nursery and also some of the flower was imported from other country. We commenced our business on 1st April 2019 and registered our business as a partnerships business. lt is equally owned and managed by four partners where each of us contributed RM5000 into our business. Our businesses were located at No.96, Ground Floor, Jalan Masjid Taman Sri Dagang, 97000 Bintulu. Belleza Florista plans to be the best flowers shop that providing a high quality of flowers in Bintulu, Sarawak. Belleza Florista also offers its products at a competitive price to meet demand of the middle to higher local market area residents and tourists.